2019
DOI: 10.1590/1983-21252019v32n425rc
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Rate of Recipient Cows After Transfer of in Vitro-Produced Nellore Embryos

Abstract: The objective of this study was to evaluate the pregnancy rate (PR) of cows of six farms in Bolivia and in the states of Acre and Rondônia in Brazil after the transfer of 4,321 in vitro Nellore embryos produced by a private company, in 2015 to 2016. The effects of the farm location, year of embryo transfer (ET), season of ET, number of previous ET per recipient, and embryo development stage on the PR of the recipient cow (chi square p<0.05) were evaluated. The PR of the six evaluated farms were similar, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…It was also determined that the embryonic developmental stages had no effect on PR during fresh embryo transfer in beef heifers. In Zebu cattle,Zuchelli et al (2019) mentioned that ET at expanded or hatched blastocyst stage resulted in higher PR (47.35%) when compared to the ET at morula or initial blastocyst (41.06%) and at blastocyst stage (43%), which did not differ from each other. Hernandez-Fonseca et al (2023) reported higher PR in RF Brahman cross-bred heifers and cows transferred with hatched blastocysts when the ET was performed with different embryo stages (blastocyst, expanded blastocysts and hatched blastocysts).…”
mentioning
confidence: 90%
“…It was also determined that the embryonic developmental stages had no effect on PR during fresh embryo transfer in beef heifers. In Zebu cattle,Zuchelli et al (2019) mentioned that ET at expanded or hatched blastocyst stage resulted in higher PR (47.35%) when compared to the ET at morula or initial blastocyst (41.06%) and at blastocyst stage (43%), which did not differ from each other. Hernandez-Fonseca et al (2023) reported higher PR in RF Brahman cross-bred heifers and cows transferred with hatched blastocysts when the ET was performed with different embryo stages (blastocyst, expanded blastocysts and hatched blastocysts).…”
mentioning
confidence: 90%
“…In vivo, embryos in the early stage of development are allocated in the oviduct, which is an extremely important organ for embryo development ( Li and Winuthayanon, 2017 ) In vitro, embryos are normally produced in 2D culture systems, using culture dishes. Although IVP is a well-established technique, some limitations need improvements, such as lower blastocyst and birth rates ( Jaguszeski et al, 2019 ), and decreased resistance to cryopreservation ( Sanches et al, 2017 ) compared with in vivo -produced embryos.…”
Section: D Culture Applied To the Female Reproductive Systemmentioning
confidence: 99%
“…Andrade et al (2012) reportaram valores de taxa de prenhez de vacas submetidas à TE de 37,6% para vacas Senepol e 39,1% para vacas Nelore. Jaguszeski et al (2019) apresentaram valores maiores ainda, 45,15% de taxa de prenhez para vacas receptoras Nelore após a TE.…”
Section: Categoriaunclassified